MUTATION OF A918C embB GENE IN ETHAMBUTOL RESISTANT Mycobacterium tuberculosis L20 ISOLATE - MEKAR SAPTARINI (NIM: 20507011), NYI
Mycobacterium tuberculosis (M. tb) is the agent that cause infectious and contagious tuberculosis (TB) disease. TB treatment must be done with accurate, complete, and regular combination of anti-TB drugs that contain isoniazid (INH), rifampicin (RIF), pyrazinamide either streptomycin or ethambutol (EMB) for the first two months, followed by combination of INH and RIF for next four months. Multi resistance M. tb for anti-TB drugs emerge due to incomplete treatment. The World Health Organization (WHO) has defined that Multi-Drug Resistant strains of M. tb (MDR-M. tb) are resistant to at least INH and RIF, while Extensively-Drug Resistant strains of M. tb is defined as strains that are also resistant to a fluoroquinolone and at least one of second-line drugs (amikasin, kanamycin, and/or capreomycin). The resistance of M. tb to EMB is caused by emb gene mutations that encodes arabinosyltransferase leading to inactive EMB to inhibit the cell wall syntesis. Mutation of A918G/C/T or G920A/C, corresponding to Met306Val/Leu or Met306Ile alteration, is mostly found on the embB gene. Our research group had isolated and characterized 42 clinical isolates of MDR-M. tb using the multiplex method of Polymerase Chain Reaction (PCR). Some of these isolates are also resistant to EMB, but have not been charaterized yet. The purpose of this work is to determine the genotypic basis of the MDR-M. tb clinical isolate which is resistant to EMB (L20).